Risk factors of lumbar lordosis and its association with lower back pain: a systematic review - Mohammad Suhaimi, Mohammad Danial Diniy; Munajat, Munayati; Bukry, Saiful Adli (IIUM Press, International Islamic University Malaysia, 2024)
Background: Low back pain (LBP) is a global health concern with significant socio-economic effects. Lumbar lordosis (LL), a curvature of the lower spine, is often implicated in LBP; however, understanding this connection requires a proper approach. Therefore, this study aimed to systematically review the scientific evidence on factors influencing the development of abnormal lordotic posture related to LBP. Method: This review analysed articles from ScienceDirect, PubMed, ProQuest and Google Scholar published between 2013 and 2023. This study screened articles, assessed eligibility based on the inclusion and exclusion criteria, and evaluated the risk of bias of the study using STROBE statement checklist. The data were then descriptively analysed. Results: Six articles were included in this systematic review. This review identified three studies that cited the nature of work and body posture, and two studies that cited gender as factors contributing to abnormal lordotic posture related to LBP. Meanwhile, another factor, age was mentioned in one study only. Conclusion: The nature of work and body posture, and gender can be considered possible risk factors for the development of abnormal lumbar lordotic posture and can cause LBP. Recognizing these risk factors would be beneficial in designing targeted preventive and therapeutic strategies, particularly for high-risk individuals.